Geologic controls on reservoir quality of the Viola limestone in Soldier Field, Jackson County, Kansas - Jensik, Chandler (Kansas State University, 2013)
Jackson County, Kansas is situated on the west side of the Forest City Basin, location of the first oil discovery west of the Mississippi River (KGS), Production in the area is predominately from the Viola Limestone, and a noticeable trend of oil fields has developed where the basin meets the Nemaha Anticline. Exploration has been sluggish, because of the lack of an exploration model. Production rates have varied widely from well to well, even when they are structurally equivalent. The goal of this study was to determine the factors controlling reservoir quality in the Ordovician-aged Viola Limestone so that a better exploration model could be developed. A two township area was studied to examine relationships between subsurface variations and production rates. In the absence of an available core through the Viola, drill cuttings were thin-sectioned and examined under a petrographic microscope to see the finer details of porosity, porosity type and dolomite crystal-size that are not visible under a binocular microscope. Production appears to be controlled by a combination of structural position and dolomite crystal size, which was controlled by secondary diagenesis in the freshwater-marine phreatic mixing zone. The best wells exhibited a Viola Limestone made up of 100% very coarsely crystalline, euhedral dolomite crystals. These wells occur on the east and southeast sides of present day anticlines, which I have interpreted to be paleo-highs that have been tilted to the east-southeast.
Keywords: Ordovician; Viola; Petroleum geology; Reservoir quality; Geology (0372); Petroleum Geology (0583)